2009
DOI: 10.1002/cncr.24233
|View full text |Cite
|
Sign up to set email alerts
|

Tissue biomarkers in renal cell carcinoma: Issues and solutions

Abstract: Renal cell carcinoma (RCC) is an aggressive malignancy associated with a high rate of metastasis. Although several promising therapeutic strategies are now available for the treatment of patients with metastatic kidney cancer, the prognosis of these patients remains poor. Research is ongoing to identify RCC-specific biomarkers that can improve early diagnosis, surveillance of tumor progression, and prediction of patient prognosis. The identification of biomarkers that may predict response to specific therapies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 77 publications
0
30
0
1
Order By: Relevance
“…This is performed by placing the sample as soon as possible into a sterile vial and DNase-free liquid under ice conditions; the temperature is extremely important, and storage must be at -80˚C after the sample has been frozen in liquid nitrogen. This ensures the transcription of genes and prevents the degradation of DNA and RNA (62).…”
Section: Discussionmentioning
confidence: 99%
“…This is performed by placing the sample as soon as possible into a sterile vial and DNase-free liquid under ice conditions; the temperature is extremely important, and storage must be at -80˚C after the sample has been frozen in liquid nitrogen. This ensures the transcription of genes and prevents the degradation of DNA and RNA (62).…”
Section: Discussionmentioning
confidence: 99%
“…It has been estimated that nearly 70% of somatic mutations present in RCC tissues are not detectable across all tumor sites. Another barrier to biomarker development is the inconsistency and variability in tissue preparation and biomarker evaluation, 97 which will affect accuracy of the biomarker data that are collected and interpreted. Efforts to define prognostic or predictive factors have largely shown that clinical features, including tumor grade, local extent of tumor, regional lymph node metastases and evidence of metastases at presentation remain the most consistent features associated with survival.…”
Section: Issues In Specific Tumor Typesmentioning
confidence: 99%
“…For example, with MRI, it is now considered that by focusing on the intracellular lipid content, intratumoral hemosiderin deposition and enhancement patterns and by using profiles in different MRI sequences (e.g., chemical shift MRI), it is possible to obtain magnetic resonance phenotypes as a biological signature of tumors (e.g., to differentiate subtypes) [14,15]. One of the major advantages of imaging biological signatures compared with traditional tissue or blood biomarkers is that the tumor is in situ and metabolically active and so will not be subject to significant bias by the lack of standardization in tissue sample acquisition, storage and ana lysis [16,17]. Imaging may also be repeated at intervals and is noninvasive, allowing development of treatment and monitoring algorithms that are commonplace in oncology.…”
Section: Biomarkers and Functional Imagingmentioning
confidence: 99%